XX festival “Zodchesvo in Siberia 2020” - Grigorieva, Elena; Shumakov, Nikolay; Posokhin, Mikhail; Tkacheva, Marina (project baikal, 2021)
The Festival “Zodchestvo of Eastern Siberia” was founded at the turn of the millennium. The first Festival was held in 2001 at Irkutsk Sibexpocenter and caused a massive outcry among the architectural community in Siberia and throughout the country.